Experimental implant evaluated in grazing yearling steers - Laudert, S.; Sauerwein, C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experimental implant containing Beta-estradiol increased (P<.05) daily gain of grazing yearling steers by 15.5% compared to controls. Compudose implants increased (P<.01) daily gain by 13.5%. There was no gain difference between the experimental implant and Compudose.
Keywords: Beef; Yearling steers; Compudose; Implants